2022
DOI: 10.1128/jvi.00594-22
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Variants of Concern Hijack IFITM2 for Efficient Replication in Human Lung Cells

Abstract: Recent data indicate that SARS-CoV-2 requires endogenously expressed IFITM proteins for efficient infection. However, the results were obtained with an early SARS-CoV-2 isolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 75 publications
1
25
1
Order By: Relevance
“…Having shown that GBPs interfere with SARS-CoV-2 spike cleavage, we sought to test whether this may sensitize SARS-CoV-2 to IFITM-mediated inhibition. IFITMs are another family of spike-targeting interferon-inducible restriction factors that can inhibit infection of a range of viruses, including SARS-CoV-2 ( 7 , 12 , 21 24 , 41 ), by perturbing viral fusion with host cell membranes and thus inhibiting infection of target cells. IFITMs are differentially localized in cells with IFITM1 being found mostly at the plasma membrane and IFITM2/3 predominantly endosomal.…”
Section: Resultsmentioning
confidence: 99%
“…Having shown that GBPs interfere with SARS-CoV-2 spike cleavage, we sought to test whether this may sensitize SARS-CoV-2 to IFITM-mediated inhibition. IFITMs are another family of spike-targeting interferon-inducible restriction factors that can inhibit infection of a range of viruses, including SARS-CoV-2 ( 7 , 12 , 21 24 , 41 ), by perturbing viral fusion with host cell membranes and thus inhibiting infection of target cells. IFITMs are differentially localized in cells with IFITM1 being found mostly at the plasma membrane and IFITM2/3 predominantly endosomal.…”
Section: Resultsmentioning
confidence: 99%
“…The exact effect of IFITM proteins during SARS-CoV-2 replication is contentious, with some studies showing that IFITM proteins inhibit cellular entry of SARS-CoV-2, in a similar manner to influenza 19 , 76 , 134 , 142 , whereas others suggest that in some contexts they enhance infection, in a manner similar to that described for OC43 and HKU1 (refs. 76 , 134 , 143 145 ). The exact role of IFITM proteins is likely to be context specific, such as the particular entry pathway used by a particular virus in a given cell type or cell line, the use of live virus versus pseudovirus and the level of IFITM protein expressed.…”
Section: Innate Immunity and Sars-cov-2 Variantsmentioning
confidence: 99%
“…Several VOCs have been shown to have different degrees of sensitivity to IFITM protein inhibition or enhancement, quite often associated with specific entry pathways or furin cleavage phenotypes. For example, Omicron, which is more efficient at endosomal entry than early variants and other VOCs, appears to show greater inhibition (or in some cases enhancement) by endosomal IFITM proteins, although this does appear to be highly dependent on the cell system used 32 , 76 , 145 . This is possibly due to Omicron either having to compromise innate evasion due to adaptive immunity avoidance, particularly in the context of vaccine-induced spike antibodies, or having to adapt to use IFITM proteins as cofactors for entry.…”
Section: Innate Immunity and Sars-cov-2 Variantsmentioning
confidence: 99%
“…However, we (almost) know with certainty that angiotensin-converting enzyme 2 (ACE2) is a crucial cell entry site for the spike (S) protein of SARS-CoV-2, and due to the high expression of ACE2 in mammalian cells, the virus can easily cause damage to multiple organs [ 11 , 12 ]. However, many other additional host factors may affect the efficacy and play roles in the COVID-19 pathogenesis, such as auxiliary SARS-CoV-2 receptors (heparan sulfate, Scavenger receptor class B member 1, neuropilin-1), alternatives to ACE2 receptors (e.g., cell surface proteins, tyrosine-protein kinase receptor UFO, low-density lipoprotein receptor class A domain-containing protein 3, C-type lectin domain family 4 member G, interferon-inducible transmembrane proteins), host proteases that mediate the viral entry via the spike (S) protein, priming–transmembrane serine protease 2 (TMPRSS2), transmembrane glycoprotein CD147, members of the phosphatidylinositol 3-kinase (PI3K) pathway, some transcriptional factors, and histone-modifying enzymes [ 13 , 14 , 15 ]. Lysosomal cysteine protease cathepsin L was also found to be a key factor in SARS-CoV-2 infection and a promising therapeutic target [ 16 ].…”
Section: Introductionmentioning
confidence: 99%